ANTARA MIMPI DAN VALIDASI: ANALISIS PENGALAMAN KEAGAMAAN SYEKH SHOLAHUDDIN FAKHRY PERSPEKTIF WILLIAM JAMES - Galbani Fadilah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the religious experiences experienced by Sheikh Sholahuddin Fakhry based on the thoughts of William James. This research method is qualitative through literature study and content analysis. The results and discussion of this study include the religious experience of Sheikh Sholahuddin Fakhry, the theory of religious experience according to William James, and the validation of Sheikh Sholahuddin Fakhry's religious experience based on the thoughts of William James. This study concludes that Sheikh Sholahuddin Fakhry's religious experience fulfills three criteria of truth according to William James, namely direct understanding, philosophical plausibility, and moral usefulness.